Biological effects of electromagnetic waves with emphasis on radio and microwave: An environmental carcinogen - Yari, Saeed; Fallah Asadi, Ayda; Mosavi Jarrahi, Alireza; Nourmohammadi, Mohammad (Asian Pacific Journal of Environment and Cancer, 2019)
Human is exposed to a variety of electromagnetic fields from natural and artificial sources. These fields cause the electric field in the body to affect the movement of ions, heat, neuromuscular stimulation, and various effects. The biological effects of these waves depend strongly on the waveform, frequency and angle between the applied fields and the Earth's magnetic field, as well as their continuity or pulsation. Electromagnetic fields caused by conventional devices are at a standard level and appear to be harmless to humans. But the results of research on specific people, such as military personnel or those who live and work near radar stations, high-pressure posts and high-powered telecommunications and radio transmitters, show that they have harmful effects and live nearby they are not risk free.